Assessing Reserve Adequacy : Specific Proposals. (Policy Papers; Policy Paper ;, 2014)
Reserves have a central place in the policy tool kit of most economies, providing insurance against shocks. In conjunction with sound policies, they can help reduce the likelihood of balance of payment crises and preserve economic and financial stability. Reserves, however, can result from both precautionary and non-precautionary policy objectives and institutional settings. While they can bring several important benefits, reserve holdings can sometimes be costly. This paper brings together recent Fund work on reserve adequacy issues aiming to strengthen their discussion in bilateral surveillance. Despite the ongoing debate on reserve issues, there is little consensus about how to assess reserve holdings in different economies, even though this is an important aspect of a member's external stability assessment. The work stream of which this paper is part aims to fill this gap by outlining a framework for discussing reserve adequacy issues in different economies. In this regard, the paper also forms part of the Fund's response to the 2012 IEO evaluation of the Fund's advice related to international reserves, which recommended, inter alia, that assessments of international reserves in bilateral surveillance reports should be more detailed and reflect country circumstances. To this end, the paper proposes that, where warranted, individual country Article IV reports include a fuller discussion of the authorities' stated objectives (precautionary and non-precautionary) for holding reserves, an assessment of the reserve needs for precautionary purposes, and a discussion of the cost of reserves. The aim would be to ensure evenhandedness so that countries with similar circumstances are assessed in similar ways, while allowing the depth and emphasis of this discussion to vary depending on country conditions and needs.